Trophic Transition Enhanced Biomass and Lipid Production of the Unicellular Green Alga Scenedesmus acuminatus - Zhang, Hu; Zhao, Liang; Chen, Yi; Zhu, Mianmian; Xu, Quan; Wu, Mingcan; Han, Danxiang; Hu, Qiang (Frontiers in Bioengineering and Biotechnology, 2021)
Microalgal heterotrophic cultivation is an emerging technology that can enable producing high cell-density algal cell cultures, which can be coupled with photoautotrophic cultivation for valuable chemicals such as lipids manufacturing. However, how the heterotrophically-grown algal cells respond to the lipid-inducing conditions has not been fully elucidated so far. In this study, when the heterotrophically-grown Scenedesmus acuminatus cells were subjected to the high light (HL) and nitrogen-limited (NL) conditions, both the biomass and lipid productivity were enhanced as compared to that of the photoautotrophically-grown counterparts. The chlorophyll a fluorometry analysis showed that the Fv/Fm and Y(II) of the heterotrophically-grown cells subjected to the HL and NL conditions was recovered to the maximum value of 0.75 and 0.43, respectively, much higher than those of the photoautotrophically-grown cells under the same stress conditions. Transcriptomic analysis revealed that heterotrophically-grown cells fully expressed the genes coding for the photosystems proteins, including the key photoprotective proteins D1, PsbS, light-harvesting-complex (LHC) I and LHC II. Meanwhile, downregulation of the carotenoid biosynthesis and upregulation of the glycolysis/gluconeogenesis, tricarboxylic acid (TCA) cycle and oxidative phosphorylation pathways were observed when the heterotrophically-grown cells were subjected to the HL and N-limited conditions for lipid production. It was deduced that regulation of these pathways not only enhanced the light utilization but also provided the reducing power and ATP by which the biomass accumulation was significantly elevated. Besides, upregulation of the acetyl-CoA carboxylase/biotin carboxylase, digalactosyl diacylglycerol synthase and diacylglycerol acyltransferase 2 encoding genes may be attributable to the enhanced lipid production. Understanding the cellular responses during the trophic transition process could guide improvement of the strength of the coupled heterotrophic and photoautotrophic cultivation for enhancing microalgal biomass and lipid production.